Telomere terminal transferase activity from Euplotes crassus adds large numbers of TTTTGGGG repeats onto telomeric primers. - Shippen-Lentz, D (1989)
A telomere terminal transferase activity was identified in developing macronuclear extracts from Euplotes crassus. The activity was essentially unregulated in vitro: up to 50 tandem repeats of the Euplotes telomeric repeat sequence TTTTGGGG were added onto synthetic telomeric oligonucleotide primers. Both the structure of the telomere substrate and its 3'-terminal sequence were recognized. The activity was destroyed by low concentrations of RNase A.